How Tense and Aspect are acquired: a cross-linguistic analysis of child Russian and English - Maria Filiouchkina (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2005)
This study examines the production of verb morphology by children acquiring two typologically different languages – Russian and English. The focus of the study is on the correlation between aspect, tense and Aktionsart in child languages. In many languages, a strong correlation has been observed in the use of the resultative Aktionsart (telic types of verbs: achievements and accomplishments) and the perfective aspect in the past tense, on the one hand, and between the non-resultative Aktionsart (atelic verbs: activities, states and semelfactives) and the imperfective aspect in the present tense, on the other.